Induction of calogenesis in leaf segment of rubber (hevea spp.) in the South-Western Amazon (Research, Society and Development, 2021)
Even considering the advances in the micropropagation studies in Hevea spp., the understanding of the stimuli and conditions necessary for the establishment of in vitro culture are still limited. One of the reasons this happens is due to the lack of an efficient protocol for the propagation of large-scale elite clones of rubber tree. In this sense, we investigated the effect of 2,4-dichlorophenoxyacetic acid on the induction of corns in leaf segments of Hevea spp., As well as the use of PPM® (Plant Preservative Mixture) in the inhibition of microbial contamination. Young rubber tree leaves were inoculated in MS (Murashig Skoog) culture medium supplemented with 2,4-D (0; 0.25; 0.5; 1.0; 2.0 and 4.0 mg L-1) with PPM® biocide (0 and 1.0-mL L-1). After 60 days it was possible to observe the highest percentage of areas and an expressive phenolic oxidation in the presence of PPM®. The 2,4-D (2.0 and 4.0 mg L-1) restrictions combined with PPM® (1 mL L-1) were effective in inhibiting microbial contamination. Callus induction occurred in the treatment containing 1 mg L-1 of 2,4-D and 1 mL L-1 of PPM® and formed a compact callus with white coloring. The protocol used in this work was efficient for disinfesting leaf explants of Hevea spp.